Cadmium Chloride Induced Histopathological Alterations in the Selected Organs of Nile tilapia Oreochromis niloticus (L.) (Bangladesh Journal of Zoology, 2024)
Histopathological alterations in the selected organs of a freshwater fish Oreochromis niloticus (L.), exposed to sub lethal concentration (17.5 ppm) of cadmium chloride (CdCl2), were studied at laboratory conditions. Static bioassay test was carried out to determine the sub lethal concentration. The changes in gill, liver, kidney, stomach and intestine of the fish were observed after 7 and 30 days exposure. The degenerative changes exhibited in fish organs were more severe and pronounced at long term exposure than that of at short term. The histopathological changes observed in the gills were fusion of secondary lamellae due to hyperplasia and hypertrophy, lifting and rupture of lamellar epithelium, oedema of primary lamellar tip, necrosis, damage of pillar cell system, congestion in blood vessels and haemorrhagic gill rays. Changes in the liver included disruption of cords, highly chromatic and irregular shaped shrunken hepatocytes, pyknotic nuclei, rupture and loss of cell boundaries, congestion in blood vessels and sinusoid, and presence of yellow brown bodies. Degeneration of tubular epithelium, tubular lumen with cellular debris, necrotic and swollen glomeruli, and haemopoietic tissue degeneration were marked in the kidney of exposed fish. Stomach tissues revealed rupture and separation of mucosal epithelium, swollen epithelial cells, degeneration of gastric gland cells, scattered blood cells all over the tissue and necrosis in the mucosal epithelium and lamina propria. In intestine, disintegration and rupture in mucosal epithelium, sloughing off epithelial and mucous cells, blood congestion in lamina propria, increased goblet cells, etc., were observed during the present study.Bangladesh J. Zool. 52(2): 237-251, 2024